2016
DOI: 10.5935/abc.20160064
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Exercise on Blood Pressure: A Meta-Analytic Investigation

Abstract: Hypertension affects 25% of the world's population and is considered a risk factor for cardiovascular disorders and other diseases. The aim of this study was to examine the evidence regarding the acute effect of exercise on blood pressure (BP) using meta-analytic measures. Sixty-five studies were compared using effect sizes (ES), and heterogeneity and Z tests to determine whether the ES were different from zero. The mean corrected global ES for exercise conditions were -0.56 (-4.80 mmHg) for systolic BP (sBP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
154
3
24

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(199 citation statements)
references
References 69 publications
18
154
3
24
Order By: Relevance
“…Esta obra está bajo una Licencia Creative Commons Atribución-NoComercial-CompartirIgual 4.0 Internacional A pesar de que un metaanálisis reciente a nivel general mostró que, indistintamente de la intensidad a la que se realiza el ejercicio, esta produce efecto hipotensor (Carpio et al, 2016), dicha generalización se debe observar con cuidado si se desea obtener el mejor resultado al prescribir el ejercicio, ya que no toma en cuenta la edad de las personas participantes en los diferentes estudios, ni el tiempo de medición de la presión arterial, ni las diferencias metodológicas en las que se realizaron las mediciones de las repeticiones máximas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Esta obra está bajo una Licencia Creative Commons Atribución-NoComercial-CompartirIgual 4.0 Internacional A pesar de que un metaanálisis reciente a nivel general mostró que, indistintamente de la intensidad a la que se realiza el ejercicio, esta produce efecto hipotensor (Carpio et al, 2016), dicha generalización se debe observar con cuidado si se desea obtener el mejor resultado al prescribir el ejercicio, ya que no toma en cuenta la edad de las personas participantes en los diferentes estudios, ni el tiempo de medición de la presión arterial, ni las diferencias metodológicas en las que se realizaron las mediciones de las repeticiones máximas.…”
Section: Discussionunclassified
“…Aunque existe evidencia científica respaldando la HPE, los estudios actualmente se enfocan en determinar cuáles son las características que debe tener el ejercicio para lograr una mayor magnitud y duración de la HPE (Carpio, Moncada, Salazar, & Solera, 2016), tanto en normotensos como en hipertensos, ya que se quiere ofrecer no solo el ejercicio como factor de protección para evitar el desarrollo de la enfermedad, sino Esta obra está bajo una Licencia Creative Commons Atribución-NoComercial-CompartirIgual 4.0 Internacional también como terapia no farmacológica para quienes ya la han desarrollado (Del Valle, et al 2015).…”
unclassified
“…63 Acutely, it has been reported reductions of BP in both aerobic and resistance training. 64,65 Chronically, previous studies found that regularly-performed PE is associated with reductions of 8.3 and 5.2 mmHg in resting systolic and diastolic BP, respectively. 66 Corroborating with this data, evidence that summarizes the effects exercise training, showing that the effects of PE reach a reduction greater than 5 mmHg on systolic blood pressure.…”
Section: Peripheral Effectsmentioning
confidence: 97%
“…Although this variability, several meta-analyses and epidemiological evidences have consistently shown a total beneficial effect of a regular physical activity [94][95][96]. A regularly performed aerobic exercise of mild to moderate intensity is effective in lowering blood pressure in hypertensive individuals for all ages and both genders.…”
Section: Physical Activitymentioning
confidence: 99%